АBOUT THE TENDENCY OF GREENING OF INTERNATIONAL MONETARY LAW - Dimitrijević, Marko B.; Golubović, Srdjan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2022)
International monetary law as a relatively young branch of law can undoubtedly contribute to solving and controlling environmental problems, taking into account the flexibility of legal norms and new tendencies in the development of discourse and normative regulation of monetary transmission mechanisms, which again points to untapped potential. A great contribution can be expected from the IMF, which in the recent period has been paying close attention to the issue of control of use and preservation of green production factors, where the need for rational use appears as their imperative in every sense, which can be read at conferences dedicated to this issue. Also, the European Central Bank is considering its potential contribution in the field of monetary policy in this context, because the legal basis for the coordination of environmental policy is present in Art. 4 of the Treaty on European Union, which explicitly establishes its competence to support and develop the general economic policy of the member states of the Union. Of course, its task in this context can never be primary, but that does not mean that it should be given up, because we think that even the smallest contribution in the field of environmental problems can certainly be established in cohesion with all other large or small contributions. the necessary balance in the use of these fragile resources in every society today (this only speaks of the complexity of the problems and the great challenges facing legislators in the world, and only cohesion and joint efforts can contribute to solving the problem in an optimal way that must always be taken into account Although the main task of subjects of international monetary law can never be to take care of the environment, this does not mean that they should not undertake any activities in this field. Certain activities of monetary agents must be undertaken primarily because and monetary and environmental policy constitutive elements of general economic policy and yes there is a high degree of synthetic dialectical connection between them. The tendency to green the monetary jurisdiction of the IMF, the World Bank, and the European Central Bank does not have to be a controversial issue, because, with the conditions of globalization of economic flows and the global financial crisis, these entities have already acquired some new fiscal competencies. The hybridization of the competencies of the main subjects of international monetary law also results from their involvement in the system of global environmental management and as such does not represent an obstacle in the implementation of basic monetary targets. In this context, the activity of the European Central Bank in undertaking activities in considering environmental risks to general economic stability and activities that increase the level of general environmental awareness is especially important. Although studies on the relationship between monetary policy and environmental issues are still at an early stage of development, it is important not to mention that the main subjects of international monetary law are increasing their efforts and clearer identification of causal mechanisms that will serve as a potential reason for adopting an eco-friendly monetary framework. Key words: international monetary law, environmental problems, Financial System Greening Network, lex monetae, European Central Bank, International Monetary Fund.